Level of Evidence of Dental Research in Saudi Arabia (2000–2020) - Mona Rajeh; Waad Khayat (International Journal of Dentistry)
Objectives. The level of evidence (LOE) of Saudi dental research from 2000 to 2020 was evaluated, and factors associated with the LOE were determined. Methods. This study was a systematic review. PubMed, Web of Science, and Medline databases were utilized to retrieve available dental articles published in English between January 2000 and May 2020. The inclusion criteria consisted of clinical studies conducted in Saudi Arabia with at least one Saudi dental affiliation. The retrieved eligible articles were evaluated independently by two reviewers using a modified Oxford LOE scale. The LOE of the studies was compared between the last two decades. Results. Of the 7237 articles identified, 1557 articles met the inclusion criteria. Approximately 78% of the published articles reported Level IV evidence. A higher trend toward Level I, II, and III publications has occurred in recent years (i.e., 2010–2020). However, no statistically significant difference existed in LOE proportions between the two decades. The presence of international collaboration and high journals’ impact factor was significantly associated with a higher LOE. Conclusion. Most published dental research studies were low LOE studies (i.e., Level IV). National and international collaboration is highly encouraged as this is a factor, according to our findings, that would be a positive addition toward publishing dental research of a higher LOE in Saudi Arabia.